- Efficacy of Tyrosine Kinase Inhibitors on serum biomarkers including thyroglobulin , thyroglobulin antibodies, and protein kinase B of Thyroid Cancer patients: Tyrosine Kinase Inhibitors on serum biomarkers - Miao, Bingliang (Journal of Medical Biochemistry, 2025)
Objective: it was to investigate the impact of the tyrosine kinase inhibitor Apatinib as an adjunct to 125I particle implantation therapy in thyroid cancer patients. Methods: data from 130 cases of thyroid cancer patients were collected. Based on treatment methods, 62 cases were categorized into the control group (CG, 125I particle implantation therapy alone) and 68 cases into the experimental group (EG, 125I particle implantation therapy + Apatinib). Clinical efficacy, thyroid function indices, ultrasound imaging features, serum biomarkers, and adverse events were compared between groups. Results: the objective response rate (82.26% vs. 73.33%) and disease control rate (91.94% vs. 80%) in EG were greatly superior to those in CG (P
Keywords: tyrosine kinase inhibitor; Apatinib mesylate; 125I particle implantation therapy; thyroid function; maximum lymph node diameter, thyroglobulin , thyroglobulin antibodies, and protein kinase B